2016
DOI: 10.1186/s13550-016-0233-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 68Ga-PSMA PET/CT on salvage radiotherapy planning in patients with prostate cancer and persisting PSA values or biochemical relapse after prostatectomy

Abstract: BackgroundSalvage radiotherapy (SRT) is clinically established in prostate cancer (PC) patients with PSA persistence or biochemical relapse (BCR) after prior radical surgery. PET/CT imaging prior to SRT may be performed to localize disease recurrence. The recently introduced 68Ga-PSMA outperforms other PET tracers for detection of recurrence and is therefore expected also to impact radiation planning.Forty-five patients with PSA persistence (16 pts) or BCR (29 pts) after prior prostatectomy, scheduled to under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 51 publications
2
78
1
2
Order By: Relevance
“…Several studies have investigated the impact of PSMA ligand PET/CT on patient management and therapy. Most studies have focused on the value of PSMA ligand PET/CT in patients with BCR after curative treatment and have reported changes in therapeutic management depending on the specific clinical scenario and the extent of treatment modification (69)(70)(71)(72)(73)(74). Most recently, an overall change in the therapeutic management of 75% of 131 patients after primary treatment was shown (69).…”
Section: Impact On Treatment Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have investigated the impact of PSMA ligand PET/CT on patient management and therapy. Most studies have focused on the value of PSMA ligand PET/CT in patients with BCR after curative treatment and have reported changes in therapeutic management depending on the specific clinical scenario and the extent of treatment modification (69)(70)(71)(72)(73)(74). Most recently, an overall change in the therapeutic management of 75% of 131 patients after primary treatment was shown (69).…”
Section: Impact On Treatment Planningmentioning
confidence: 99%
“…Similar results were found in a smaller cohort of 45 patients, resulting in a change of treatment in 19 of 45 patients (42.2%), including extension of radiotherapy field or administration of dose escalation subsequent to local recurrence. In 2 of 19 patients, salvage radiotherapy was replaced by systemic treatment due to multiple metastatic lesions (70). In a well-defined patient cohort before salvage radiotherapy, a major management change in 20 of 70 patients (28.6%) with a PSA level of less than 1 ng/mL was demonstrated by van Leeuwen et al (74).…”
Section: Impact On Treatment Planningmentioning
confidence: 99%
“…Retrospective comparison studies have demonstrated PSMA PET may outperform F18-choline, can impact salvage radiotherapy treatment planning, and may guide use of stereotactic body radiation therapy (SBRT) for oligometastatic treatment. [54][55][56][57] Critical validation studies are needed. Recently, PSMA PET has been shown to improve initial staging of prostate cancer compared with MRI and provides complimentary information when utilized together.…”
Section: Molecular Imaging In Prostate Cancermentioning
confidence: 99%
“…The clinical utility and its ability to impact treatment decisions are less established and are the focus of multiple ongoing clinical trials (NCT02981368, NCT02825875). Retrospective comparison studies have demonstrated PSMA PET may outperform F18‐choline, can impact salvage radiotherapy treatment planning, and may guide use of stereotactic body radiation therapy (SBRT) for oligometastatic treatment . Critical validation studies are needed.…”
Section: Introductionmentioning
confidence: 99%
“…The trend to treat oligometastatic disease with focally directed radiation technologies is coming at a time when imaging technologies are detecting more areas of asymptomatic disease, and systemic or targeted therapies are allowing patients to continue treatment longer than ever before, tempting clinicians to treat limited metastatic disease more aggressively despite the relative lack of highlevel evidence. In prostate cancer, Ga-PSMA PET scans are detecting areas of distant, low volume disease before biochemical failure after primary radiation or surgery and are radically changing patterns of clinical decisionmaking (19). In breast cancer, advances in systemic therapies have significantly improved survival for those with metastatic disease.…”
mentioning
confidence: 99%